A Corpus-Based Exploration of the Discourse Marker Well in Spoken Interlanguage. (September 2019) - Huang, Lan-fen
This corpus-based study examines the widely-used discourse marker well in Chinese-speaking learners' speech and compares its frequencies in native speaker data and Swedish learners. While Swedish learners overuse well, Chinese-speaking learners (predominantly at the upper-intermediate level) significantly underuse it. The positions and functions of well are further examined using a functional framework. One-fourth of the Chinese-speaking learners who use well manipulate its positions in utterances in a similar way to native speakers. In terms of functions, well is employed for speech management much more frequently than for attitudinal purposes. The greater use of the former does not generally create negative effects, but the under-representation of the latter may suggest that Chinese-speaking learners sound too direct in certain contexts. The paper concludes by considering pedagogical implications for different first languages and proficiency levels and their possible applications to the instruction of well .